2013
DOI: 10.1159/000343348
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Renin Release via Cyclic ADP-Ribose-Mediated Signaling: Evidence from Mice Lacking CD38 Gene

Abstract: Background/Aims: Despite extensive studies, the intracellular regulatory mechanism of renin production and release is still poorly understood. The present study was designed to test whether CD38-ADP-ribosylcyclase signaling pathway contributes to the regulation of renin production and release, and to examine whether CD38 gene knockout (CD38-/-) can change this important renal endocrinal function. Methods: ADP–ribosylcyclase activity was estimated utilizing HPLC, cADPR levels from western blot, plasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…Indeed, cADPR is a potent Ca 2+ -releasing agent acting through ryanodinesensitive, inositol 1,4,5-trisphosphate (IP 3 )-independent intracellular stores involved in a number of biological functions both in human and mouse (31). CD157mediated biological functions include lymphocyte proliferation (32,33), cardiac and intestinal longitudinal muscle contraction (34,35), activation of airway smooth muscle cells (36), inhibition of the cardiomyogenesis of mouse embryonic stem cells (37), glucose-induced insulin release in the endocrine pancreas (38,39), and regulation of renal hemodynamics and excretory function in mice (40).…”
Section: Cd157 Enzymatic Functionsmentioning
confidence: 99%
“…Indeed, cADPR is a potent Ca 2+ -releasing agent acting through ryanodinesensitive, inositol 1,4,5-trisphosphate (IP 3 )-independent intracellular stores involved in a number of biological functions both in human and mouse (31). CD157mediated biological functions include lymphocyte proliferation (32,33), cardiac and intestinal longitudinal muscle contraction (34,35), activation of airway smooth muscle cells (36), inhibition of the cardiomyogenesis of mouse embryonic stem cells (37), glucose-induced insulin release in the endocrine pancreas (38,39), and regulation of renal hemodynamics and excretory function in mice (40).…”
Section: Cd157 Enzymatic Functionsmentioning
confidence: 99%
“…In addition, several studies have suggested the regulation of Ren to be controlled by the CD38-cyclic ADP-ribose (cADPR)-mediated signaling pathway [ 5 ]. cADPR serves as a second messenger in terms of controlling the intracellular Ca 2+ concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies using CD38 knockout mice have suggested that CD38/cADPR system plays important roles in neutrophils death by infection [ 113 ], autoimmune diabetes [ 114 ], and renal hemodynamics and excretory function [ 115 ]. However, there have been only quite limited studies on the roles of CD38/cADPR system in CNS.…”
Section: Roles Of Cd38 In Cell Death and Ischemic Brain Injurymentioning
confidence: 99%